1988
DOI: 10.1073/pnas.85.17.6518
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the human anionic glutathione S-transferase cDNA and the relation of its gene expression to estrogen-receptor content in primary breast cancer.

Abstract: The development of multdrug iresisance in MCF7 human breast cancer cells is acted with ovexpression of P-glycoprotein, changes in activities of several deo don enzymes, and loss of hornmoe senivity and etg receptors (ERs). We In vitro exposure of cancer cells to certain cytotoxins not only leads to resistance of the cells to the selecting agent but can also lead to broad crossresistance to structurally dissimilar cytotoxins (1-7). This phenomenon of multidrug resistance has been associated with decreased int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
48
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 36 publications
3
48
1
1
Order By: Relevance
“…Our results concerning GSTp mRNA levels are in accordance with those published by Moscow et al (1988). However, as reported by Shea et al (1990) and Peters et al (1993), we did not find any relationship between GSTp expression and hormone receptor status.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results concerning GSTp mRNA levels are in accordance with those published by Moscow et al (1988). However, as reported by Shea et al (1990) and Peters et al (1993), we did not find any relationship between GSTp expression and hormone receptor status.…”
Section: Discussionsupporting
confidence: 92%
“…However, as reported by Shea et al (1990) and Peters et al (1993), we did not find any relationship between GSTp expression and hormone receptor status. Such a result is at variance with previous reports (Moscow et al, 1988;Gilbert et al, 1993). In addition, we also showed that diploid tumours exhibited higher GSTp mRNA levels than aneuploid tumours.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…A significant increase in GSTi expression was observed following tamoxifen treatment. GSTx gene is highly expressed in ER-negative breast cancer cell lines (Morrow et al, 1992) and tumours (Howie et al, 1989;Moscow et al, 1988;Gilbert et al, 1993). Comparing ER-and ER' cell lines, Morrow et al (1992) showed that endogenous GSTi gene transcription rates are similar in both cell lines but the stability of endogeneous GSTi mRNA is extraordinarily higher in ER-negative cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the nucleotide sequences of the complete human GST Pi cDNA and GST Pi gene reported from different laboratories (23)(24)(25)(26) have been identical, leading to the notion that only one human GST Pi gene exists (5). The isolation of two different GST Pi proteins from human placenta (27), however, strongly indicates that genetic polymorphism may exist in the human GST Pi gene locus.…”
mentioning
confidence: 96%